P53-mediated G1 arrest requires the induction of both p21 and Killin in human colon cancer cells. Issue 2 (17th January 2022) - Luo, Dan; Yu, Chune; Yu, Jing; Su, Chao; Li, Shun; Liang, Peng
ABSTRACT: The main biological function of the tumor suppressor p53 is to control cell cycle arrest and apoptosis. Among the p53 target genes, p21 has been identified as a key player in p53-mediated G1 arrest, while Killin, via its high DNA binding affinity, has been implicated in S and G2/M arrest. However, whether Killin is involved in G1 arrest remains unclear. This research aimed to explore the role of Killin in p53-mediated G1 arrest. Knockout of killin in human colorectal cells led to a dramatic decrease in p53-mediated G1 arrest upon DNA damage. Moreover, double knockout of killin and p21 completely abolished G1 arrest, similar to that of p53 knockout cells. We further showed that Killin could upregulate p21 protein expression independent of p53 via ubiquitination pathways. Immunoprecipitation studies indicated that Killin may directly bind to proteasome subunits, thereby disrupting proteasomal degradation of p21. Together, these results demonstrate that Killin is involved in multiple cell cycle checkpoint controls, including p53-mediated G1 arrest.